Expression of TWISTED DWARF1 lacking its in‐plane membrane anchor leads to increased cell elongation and hypermorphic growth. (9th December 2013) - Bailly, Aurélien; Wang, Bangjun; Zwiewka, Marta; Pollmann, Stephan; Schenck, Daniel; Lüthen, Hartwig; Schulz, Alexander; Friml, Jiri; Geisler, Markus
Summary Plant growth is achieved predominantly by cellular elongation, which is thought to be controlled on several levels by apoplastic auxin. Auxin export into the apoplast is achieved by plasma membrane efflux catalysts of the PIN‐FORMED (PIN) and ATP‐binding cassette protein subfamily B/phosphor‐glycoprotein (ABCB/PGP) classes; the latter were shown to depend on interaction with the FKBP42, TWISTED DWARF1 (TWD1). Here by using a transgenic approach in combination with phenotypical, biochemical and cell biological analyses we demonstrate the importance of a putative C‐terminal in‐plane membrane anchor of TWD1 in the regulation of ABCB‐mediated auxin transport. In contrast with dwarfed twd1 loss‐of‐function alleles, TWD1 gain‐of‐function lines that lack a putative in‐plane membrane anchor (HA–TWD1‐Ct) show hypermorphic plant architecture, characterized by enhanced stem length and leaf surface but reduced shoot branching. Greater hypocotyl length is the result of enhanced cell elongation that correlates with reduced polar auxin transport capacity for HA–TWD1‐Ct. As a consequence, HA–TWD1‐Ct displays higher hypocotyl auxin accumulation, which is shown to result in elevated auxin‐induced cell elongation rates. Our data highlight the importance of C‐terminal membrane anchoring for TWD1 action, which is required for specific regulation of ABCB‐mediated auxin transport. These data support a model in which TWD1 controls lateral ABCB1‐mediated export into the apoplast, which is required for auxin‐mediated cell elongation.